Orbitally universal centers. (June 2020) - Algaba, Antonio; García, Cristóbal; Giné, Jaume; Llibre, Jaume
Abstract: In this paper we define when a polynomial differential system is orbitally universal and we show the relevance of this notion in the classical center problem, i.e. in the problem of distinguishing between a focus and a center.